Odpowiedź :
Odpowiedź:
3x - (3 - 2x) = 5 - (x - 6)
3x - 3 + 2x = 5 - x + 6
5x + x = 11 + 3
6x = 14 /:6
x = 14/6 = 2 2/6 = 2 1/3
7- x - 3/2 = 5x - (2 - 3x)
-x + 7 - 1 1/2 = 5x - 2 + 3x
-x - 8x = -2 - 5 1/2
-9x = -7 1/2 /:(-9)
x = 15/2 * 1/9 = 5/6
Szczegółowe wyjaśnienie:
[tex]3x - (3 - 2x) = 5 - (x -6) \\ 3x - 3 + 2x = 5 - x + 6 \\ 3x + 2x + x = 6 + 5 + 3 \\ 6x = 14 \: \: | \div 6 \\ x = 2 \frac{1}{3} [/tex]
[tex]7 - x - \frac{3}{2} = 5x - (2 - 3x) \\ 7 - x - \frac{3}{2} = 5x - 2 + 3x \\ - x - 5x - 3x = - 2 - 7 + \frac{3}{2} \\ - 9x = - 9 + \frac{3}{2} \\ - 9x = - 7.5 \: \: | \div ( - 9) \\ x = \frac{5}{6} [/tex]